Effect of cold water immersion on repeat cycling performance and thermoregulation in the heat - Vaile, J.; Halson, J.; Gill, N.; Dawson, B. (Journal of Sports Sciences, 2008)
To assess the effect of cold water immersion and active recovery on thermoregulation and repeat cycling performance in the heat, ten well-trained male cyclists completed five trials, each separated by one week. Each trial consisted of a 30-min exercise task, one of five 15-min recoveries (intermittent cold water immersion in 10°C, 15°C and 20°C water, continuous cold water immersion in 20°C water or active recovery), followed by 40 min passive recovery, before repeating the 30-min exercise task. Recovery strategy effectiveness was assessed via changes in total work in the second exercise task compared with that in the first. Following active recovery, a mean 4.1% (s = 1.8) less total work (P = 0.00) was completed in the second than in the first exercise task. However, no significant differences in total work were observed between any of the cold water immersion protocols. Core and skin temperature, blood lactate concentration, heart rate, rating of thermal sensation, and rating of perceived exertion were recorded. During both exercise tasks there were no significant differences in blood lactate concentration between interventions; however, following active recovery blood lactate concentration was significantly lower (P < 0.05; 2.0 ± 0.8 mmol · l-1) compared with all cold water immersion protocols. All cold water immersion protocols were effective in reducing thermal strain and were more effective in maintaining subsequent high-intensity cycling performance than active recovery.